2019
DOI: 10.2217/fon-2019-0180
|View full text |Cite
|
Sign up to set email alerts
|

ATTAIN: Phase III Study of Etirinotecan Pegol Versus Treatment of Physician’s Choice in Patients with Metastatic Breast Cancer and Brain Metastases

Abstract: The increasing incidence of breast cancer brain metastases is a major clinical problem with its associated poor prognosis and limited treatment options. The long-acting topoisomerase-1 inhibitor, etirinotecan pegol, was designed to preferentially accumulate in tumor tissue including brain metastases, providing sustained cytotoxic SN38 levels. Motivated by improved survival findings from subgroup analyses from the Phase III BEACON trial, this ongoing randomized, Phase III trial compares etirinotecan pegol to dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…17 NKTR102 (etirinotecan pegol), an irinotecan conjugated, via a proprietary biodegradable ester-based linker, to polyethylene glycol (PEG), with extended release characteristic has reached phase III clinical trials to treat metastatic breast cancer. 18,19 In this study, mPEG-PLGA was synthesized using green chemistry requiring minimal purification steps. mPEG-PLGA polymeric nanoparticles were formulated using nanoprecipitation method and two types of hydrophilic surfactants namely Tween® 80 (T-NP-Ir) and Pluronic® F-127 (P-NP-Ir), for irinotecan (NP-Ir) delivery to colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…17 NKTR102 (etirinotecan pegol), an irinotecan conjugated, via a proprietary biodegradable ester-based linker, to polyethylene glycol (PEG), with extended release characteristic has reached phase III clinical trials to treat metastatic breast cancer. 18,19 In this study, mPEG-PLGA was synthesized using green chemistry requiring minimal purification steps. mPEG-PLGA polymeric nanoparticles were formulated using nanoprecipitation method and two types of hydrophilic surfactants namely Tween® 80 (T-NP-Ir) and Pluronic® F-127 (P-NP-Ir), for irinotecan (NP-Ir) delivery to colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the presence of BM usually confers a worse prognosis, the results in breast cancer suggest that patients with these lesions derive at least the same relative magnitude of benefit from treatment than patients without BM. Of note, the findings from one of the trials shown in Table 1 [ 17 ] led the authors to design a new phase 3 trial of the same agent exclusively among patients with BM [ 29 ]. Likewise, ongoing combination therapy trials for patients with BM from breast cancer have been recently summarized [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the BEACON trial (a phase III trial), BCBM patients who received NKTR-102 treatment had a markedly lowered death risk than those who received treatment of physician's choice (TPC) (HR 0.51; P < 0.01), with median OS of 10.0 and 4.8 months, respectively (81). In ATTAIN trial, a phase III study of NKTR 102 versus TPC in metastatic BC patients (82), the median PFS in BM patients of NKTR 102 and TPC was 3.9 and 3.3 months, respectively (HR, 0.59; 95% CI, 0.33-1.05; P =0.07), and the median OS in both the groups was nearly the same (7.8 months for NKTR 102, and 7.5 months for TPC group; HR=0.90; 95% CI, 0.61-1.33; P =0 .60) (83). The ATTAIN randomized clinical trial was not consistent with the positive OS benefit observed in BEACON trial (81,83).…”
Section: Treatment For Triple-negative Bcbm 41 Chemotherapymentioning
confidence: 99%